Understanding investor interaction with firm information: A discussion of Lee and Zhong (2022) - Blankespoor, Elizabeth (Journal of Accounting and Economics, 2022)
Investors are central to the incorporation of firm information in capital markets, yet it is challenging to observe the particular information they use and struggle with. Lee and Zhong (2022) use online investor interactions with Chinese public firms to document evidence that investors face significant processing costs. They find that when investor interactions occur, capital markets behave as if the information environment has improved, with increased trading activity, liquidity, and timely pricing of the quarter's earnings in returns. My discussion highlights the contributions of Lee and Zhong's findings to the processing cost, retail investor, and investor interactions literatures. I also describe empirical challenges faced by this and similar studies. I encourage using the details of interactions to disentangle the nature of processing costs and to increase support for causal conclusions more generally. Finally, I note several topics related to investor interaction that would benefit from further research.